(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Tourism in India hasregistered significant growth in the recent years. In 1951, internationaltourist arrival stood at around 17 thousand only while the same has now gone upto 3.91 million in 2005. The upward trend is expected to remain firm in thecoming years. Tourism is the third largest net earner of foreign exchange forthe country recording earnings of US 5731 million in 2005, a growth of 20.2percent over 2004. Tourism is also one of the sectors, which employs thelargest number of manpower. According to the Ministry of Tourism, duringJanuary - December of the calendar year 2006 total tourist inflow stood at44,299,15 as against 39,186,10 in the same period of the last year. The totalforeign exchange earnings earned during January- December of the calendar year2006 stood at US 6569.34 million against US 5730.86 million for the sameperiod in 2005. Tourism sector holds immense potential for Indian economy. Itcan provide impetus to other industries through backward and forward linkagesand can generate huge revenue earnings for the country. In the recent 2007-08budget, the provision for building tourist infrastructure has been increasedfrom US 95.6 million in 2006-07 to US 117.5 million in 2007-08.